2006
DOI: 10.1016/j.jcrs.2006.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the posterior cornea after laser in situ keratomileusis and photorefractive keratectomy

Abstract: There was no statistically significant difference in posterior corneal displacement between the LASIK and PRK patients. The changes in PRK and LASIK eyes appeared to be within acceptable measurement variation. Contrary to previous reports, ectatic changes to the posterior corneal surface did not routinely occur after LASIK surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 21 publications
4
64
2
1
Order By: Relevance
“…There are a number of possible causes for this measured change in internal HOA. A change may occur to the posterior cornea [21,22], which is supported by slit-scanning topography studies indicating changes occur to the posterior cornea following LASIK [24][25][26][27][28][29][30][31][32][33][34][35][36]. However, some slit-scanning topography studies have found no changes to the posterior cornea post-LASIK [37,38], and Ueda et al [39] demonstrated that these posterior corneal changes are artefacts due to changes in the magnification ratio.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of possible causes for this measured change in internal HOA. A change may occur to the posterior cornea [21,22], which is supported by slit-scanning topography studies indicating changes occur to the posterior cornea following LASIK [24][25][26][27][28][29][30][31][32][33][34][35][36]. However, some slit-scanning topography studies have found no changes to the posterior cornea post-LASIK [37,38], and Ueda et al [39] demonstrated that these posterior corneal changes are artefacts due to changes in the magnification ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Pentacam is distinguished from other topographic systems by its ability to evaluate the entire anterior eye segment in a single scan without contact with the cornea. Pentacam has been utilized to measure various parameters including corneal curvature and elevation at the front and back surfaces [15][16][17][18], corneal thickness [19,20], anterior chamber depth (ACD) and other anterior segment parameters including anterior chamber volume (ACV) and anterior chamber angle (ACA) [21][22][23][24]. However, no study has used Pentacam for investigating the effects of pterygium and its excision on the front and back corneal surfaces and anterior segment parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of recent studies [15][16][17][18] have shown that the posterior corneal surface was barely changed by refractive surgery; therefore, we speculate that the anterior corneal surface alone is sufficient to reflect the surgically induced refractive changes. Therefore, only the radius change in the curvature of the anterior corneal surface was considered in the present study.…”
Section: Discussionmentioning
confidence: 82%